A New Caremark Era: Causes and Consequences - Roy Shapira (Washington University Law Review, 2021)
What role does corporate law play in holding directors accountable for compliance failures? Until recently, the answer has been “very little.” The prevalent standard for director oversight duties (Caremark duties) was set high, effectively demanding that plaintiffs show scienter without having access to discovery. As a result, derivative actions over directors’ failure of oversight were routinely dismissed at the pleading stage, and many commentators considered Caremark duties largely irrelevant. Yet starting in June 2019, a string of successful Caremark cases have signaled a new era of enhanced oversight duties. This Article contributes to our understanding of the new Caremark era along three dimensions. First, the Article delineates the contours of the shift in Delaware courts’ approach to oversight duties. The courts now increasingly apply the “mission critical compliance” exception to justify enhanced duties, and lower the threshold for receiving information in order to investigate potential failure-of-oversight claims. Second, the Article identifies the drivers of this “new Caremark era,” with special emphasis on the role of a seemingly disparate development in shareholders’ right to information from the company. Shareholders now enjoy much better pre-filing discovery powers, which they can utilize to plead with particularity facts about how the board never even discussed a critical compliance issue, or how they knew about critical problems but chose to ignore them. Armed with these newfound pre-filing investigatory tools, shareholders can overcome what once seemed insuperable pleading hurdles. Finally, the Article evaluates the desirability of the new Caremark era, spotlighting its likely positive effects on information flows inside companies and the ability of the market to discipline corporate misbehavior (better reputational discipline), as well as the ways in which it nicely compensates for the blind spots of other enforcement mechanisms.
Keywords: Corporate law; Caremark duties; Shareholder litigation; Director oversight liability; In re Caremark Int’l Inc. Derivative Litigation 698 A2d 959; Shareholder inspection rights; DGCL 220